1999
DOI: 10.1177/0011128799045004004
|View full text |Cite
|
Sign up to set email alerts
|

Sentence Completion and Recidivism among Juveniles Referred to Teen Courts

Abstract: This study focuses on sentence completion and recidivism of juveniles referred to teen courts for disposition by their peers as an alternative to judicial sentencing. More than 70 percent of the referrals completed their sentences, and just less than a third recidivated over a 1-year follow-up. In multivariate models, sentence completion was significantly less likely among persons sentenced to community service, and recidivism was significantly higher among juveniles with prior records and those who were sente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 9 publications
3
47
1
Order By: Relevance
“…Some researchers have reported on TC completion and recidivism rates. Completion rates between 71 percent and 92 percent and recidivism rates between 10 percent and 32 percent have been reported (Harrison, Maupin, & Mays, 2001;Hissong, 1991;Minor, Wells, Soderstrom, Bingham, & Williamson, 1999;Rasmussen, 2004;Seyfrit, Reichel, & Stutts, 1987). Unfortunately, because prior evaluations have generally used less than optimal research designs and varying definitions of recidivism with vague descriptions of the follow-up period, it is difficult to determine the actual effectiveness of TCs for reducing subsequent crime.…”
Section: Previous Research On Teen Courtmentioning
confidence: 99%
“…Some researchers have reported on TC completion and recidivism rates. Completion rates between 71 percent and 92 percent and recidivism rates between 10 percent and 32 percent have been reported (Harrison, Maupin, & Mays, 2001;Hissong, 1991;Minor, Wells, Soderstrom, Bingham, & Williamson, 1999;Rasmussen, 2004;Seyfrit, Reichel, & Stutts, 1987). Unfortunately, because prior evaluations have generally used less than optimal research designs and varying definitions of recidivism with vague descriptions of the follow-up period, it is difficult to determine the actual effectiveness of TCs for reducing subsequent crime.…”
Section: Previous Research On Teen Courtmentioning
confidence: 99%
“…Many TC studies have not used comparison groups, thus limiting their ability to assess the program's effectiveness (e.g., Forgays et al 2004;Garrison 2001;Harrison et al 2000;Minor et al 1999). Minor et al (1999) examined TC respondents over three different time periods and found a recidivism rate of 31.1%.…”
Section: Teen Courts: Description and Previous Researchmentioning
confidence: 99%
“…Minor et al (1999) examined TC respondents over three different time periods and found a recidivism rate of 31.1%. Unfortunately, without a comparison group, it is not possible to know whether TC reduced, did not effect, or aggravated recidivism as compared with alternative sanctioning programs.…”
Section: Teen Courts: Description and Previous Researchmentioning
confidence: 99%
“…There are different ways peer courts receive their referrals; for example, some are preadjudicatory, whereas others are postadjudicatory. In addition, some peer courts are adversarial, whereas others are not (Minor, Wells, Soderstrom, Bingham, & Williamson, 1999).…”
Section: Introductionmentioning
confidence: 99%